Project Report on Real time Controller using Microprocessor - ALEX VARGHESE, V-NOD G and B R SUBRAMANYESWARA RAO (1990)
INTERNAL GUIDE:M ANANTHARAM, MVJCE EXTERNAL GUIDE:V SHYAM, HOD OF ELECTRONICS MSRIT
Keywords: Real time Controller using Microprocessor